2009
DOI: 10.1673/031.009.1501
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extracts of Some Medicinal Plants are as Toxic as Lmidacloprid to the Sweet Potato Whitefly,Bemisia tabaci

Abstract: Aqueous extracts of nine plants, known to have medicinal activity, were tested for their toxicity against the sweet potato whitefly, Bemisia tabaci Genn. (Homoptera: Aleurodidae) compared to the toxicity of the insecticide, Imidacloprid. Extracts of Lepidiuim sativum L. (Brassicales: Brassicaceae) killed 71 % of early stage nymphs, which was not significantly different from mortality caused by Imidacloprid. Treatment of pupae with three plant extracts, L. sativum, Achillea biebersteinii L. (Asterales: Asterace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
0
23
2
5
Order By: Relevance
“…It is also important to note the lethal effect of the fumitory extract on the different life stages of the pest. Ateyyat et al (2009) reported that the highest percentage of mortality of eggs cotton whitefly (CWF) (20%) was caused by the extract of Euphorbia hierosolymitana. Al-mazra'awi et al (2009) evaluated insecticidal and repellent activities of medicinal plant extracts against the sweet potato whitefly, B. tabaci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note the lethal effect of the fumitory extract on the different life stages of the pest. Ateyyat et al (2009) reported that the highest percentage of mortality of eggs cotton whitefly (CWF) (20%) was caused by the extract of Euphorbia hierosolymitana. Al-mazra'awi et al (2009) evaluated insecticidal and repellent activities of medicinal plant extracts against the sweet potato whitefly, B. tabaci.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that this extract not only caused death at the immature stages but also caused shorter life duration and decreased female density. Based on the research of Ateyyat et al (2009), Lepidium sativum extract with 71% casualties, caused the highest mortality on early stage nymph. Al-mazra'awi et al (2009) demonstrated that extracts from the plants Ruta chalepensis, Peganum harmala and A. strigosa were the most promising extracts for the control of B. tabaci resulting in more than a 50% mortality of the immature stages.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, [54] emphasized that the high pesticide effect or the activity of the crude oil fumigants of Artemisia plants on Callosobruchus maculates , Sitophilus oryzae and Tribolium castanium beetles was LC50.…”
Section: Discussionmentioning
confidence: 99%
“…[6] For example, Kordan et al [7] found the deterrent properties of Achillea millefolium L. against Sitophilus granaris L. and Tribolium castaneum Herbest. Ateyyat et al [8] studied the effect of A. biebersteinii L. on adults of sweet potato whitefly, Bemisia tabaci Genn. The medicinal plants, Artemisia annua L. and A. millefolium have been reported deterrence activities against Pieris rapae L. [9] Beside essential oils, repellent potential of certain plant extracts such as thyme oil and some of its effective substances are known from the work of other authors.…”
Section: Introductionmentioning
confidence: 99%